Movimento higienista: construção da figura feminina - Silva, Poliana Moreira (2017)
Introduction: the role attributed to women has been built since ancient Greece. And we have in the Hygienist Movement that emerged in Brazil in the late nineteenth and early twentieth centuries, the reaffirmation of concepts related to the role attributed to women. Objectives: To understand and analyze how women's magazines and Health Manuals were influenced by the Hygienist Movement and how it influenced the formulation of rules, norms and behaviors for women to live and behave in society. Material and methods: a qualitative, descriptive, documentary and retrospective study was performed through the reading of “O Cruzeiro" and "Jornal das Moças" magazines of the 1950s and of the Health Manuals of the 1960s. The journals used in the research were consulted via Web (Brazilian Digital Hemeroteca). The volumes of the journals were randomly selected through a simple lottery, in which five volumes of each of the journals were chosen according to each year of the 50s. The Health Manuals, however, are domain documents which were made in the school subject of Science by students who did the Magisterium course. After reading the sources searched, the texts and the images were analyzed using the content analysis. Results: women's magazines from the 1950s were important sources of information for Brazilian women. They revealed transformations and permanences in customs, family relations, social norms and rules of behavior, images and roles attributed to men and women. The Health Manuals, although they were made by students, show practically the same themes as the researched journals. Thus, we note the influence of the Hygienist Movement in the researched sources. Conclusion: Women's magazines and Health Manuals used in research served as guides to social, family and religious behavior, reinforcing the idealized or expected role of women in society. The Hygienist Movement in Brazil contributed to the formulation of rules, norms and behaviors for women to live and behave in society, as well as for the construction of the female model by great influence of women's magazines and Health Manuals.